2013
DOI: 10.1186/1750-1172-8-76
|View full text |Cite
|
Sign up to set email alerts
|

The internet user profile of Italian families of patients with rare diseases: a web survey

Abstract: BackgroundThe use of the Internet for searching and sharing health information and for health care interactions may have a great potential for families of children affected with rare diseases. We conducted an online survey among Italian families of patients with rare diseases with the objective to describe their Internet user profile, and to explore how Internet use affects their health decisions.MethodsAll members of UNIAMIO FIMR, a federation of associations of patients with rare diseases, were invited via m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 19 publications
0
75
0
6
Order By: Relevance
“…Due to scarce knowledge about rare diseases and insufficient information provision by health care providers, many information needs of rare disease patients are unmet and patients are often forced to seek health information on their own. For many patients, personal contacts, either through patient associations or online, played a major role in information acquisition (Fox, ; Huyard, ; Limb et al., ; Litzkendorf et al., ; Morgan et al., ; Pauer et al., ; Tozzi et al., ). Our findings are consistent with the results of previous studies, but provide additional insights into information behaviour of rare disease patients, and especially the role of connecting and peer‐to‐peer information sharing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to scarce knowledge about rare diseases and insufficient information provision by health care providers, many information needs of rare disease patients are unmet and patients are often forced to seek health information on their own. For many patients, personal contacts, either through patient associations or online, played a major role in information acquisition (Fox, ; Huyard, ; Limb et al., ; Litzkendorf et al., ; Morgan et al., ; Pauer et al., ; Tozzi et al., ). Our findings are consistent with the results of previous studies, but provide additional insights into information behaviour of rare disease patients, and especially the role of connecting and peer‐to‐peer information sharing.…”
Section: Discussionmentioning
confidence: 99%
“…We know from previous studies that patients actively engage in seeking health information right after diagnosis with disease prognosis being their primary information need at first (Fox, ; Limb et al., ; Litzkendorf et al., ; Morgan et al., ; Tozzi et al., ). Our study confirms this, but shows as well that the chronic nature of rare conditions, not knowing their causes, and not having a specific cure, is motivation for seeking health information continuously.…”
Section: Discussionmentioning
confidence: 99%
“…9 Given this enormous number of potential study subjects, medicine has a growing interest in the use of social media in the context of research. One study showed that families dealing with rare diseases are active in social media communities, 10 and a few reports demonstrate the use of social media to recruit subjects for broad population-based studies, studies of more common diseases, or small studies of less common diseases. [11][12][13][14] To our knowledge, only 1 study has reported using primarily social media in a prospective study of a very rare disease: an online support group of 12 individuals was accessed to obtain consent for a study of spontaneous coronary artery dissection.…”
Section: Lessons Learned and Future Possibilitiesmentioning
confidence: 99%
“…Although the information in no way diminishes the necessity for professional advice and counselling, families provided with improved online information about emerging clinical research may develop a deeper understanding and therefore be better equipped to discuss matters and concerns with their health care providers [37-39]. Ideally, the information presented would accelerate the dissemination of information about identification of beneficial approaches to the disorder, such as available treatments, dietary changes, or useful devices [39,40]. …”
Section: Discussionmentioning
confidence: 99%